관광객 선호도 비교·분석을 통한 지역축제 발전방안 : 서부경남 문화관광축제를 중심으로 - 류정섭 (2010)
The purpose of this paper is to present development plans by comparing the preferences of tourists for the local festivals designated by the Ministry of Culture, Sports and Tourism, being held in western Gyeongnam Province. This study examines any difference of preferences in regional festivals using the Thurstone Case V Scale and the fitness test using the Pearson’s goodness-of-fit test. And we would like to verify the most important factor in expressing the preference degree. The results were as follows: (1) the general tourists to the regional festivals showed the most preference for JinJu Namgang Yudeung Festival. (2) the differentiation of main program had a critical effect on the difference of preference for regional festivals. (3) the preference for the wellbeing-oriented SanCheong Oriental Medicinal Herb Festival has increased. (4) in the case of Hadong Wild Tea and Culture Festival, it is necessary to improve tourist preferences and the strategies to increase the loyalty of the wild tea and culture mania class. Therefore, to make the festivals preferred by tourists, festival managers need to continue to do their best to make the festivals have killer contents by improving the main program of each festival.
Keywords: 지역축제선호도비교; 서스톤 V 척도; 적합도 검정; 지역축제발전방안; regional festival preferences comparison; Thurstone Case V Scale; goodness-of-fit test; regional festival development plan